2022
DOI: 10.3390/chemosensors10110478
|View full text |Cite
|
Sign up to set email alerts
|

Development and Field Validation of Low-Cost Metal Oxide Nanosensors for Tropospheric Ozone Monitoring in Rural Areas

Abstract: This work describes the technical features and the performance of two different types of metal-oxide semiconductor sensors, based on ZnO:Ga thin films and SnO2-G nanofibrous layers, for tropospheric ozone monitoring in ambient air. These nanostructures were tested and compared with commercial metal-oxide semiconductor sensors under controlled laboratory conditions and in a field campaign during summer 2021 in Monfragüe National Park (western Spain). The paper also details the design of the electronic device de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…The materials were tested and compared with commercial SMOX sensors under both controlled laboratory conditions and real-life conditions. Promising results were obtained, which showed that the prepared sensors performed similarly to the commercial sensors and exhibited excellent performance compared to the usual commercial sensors [33].…”
Section: Introductionmentioning
confidence: 81%
“…The materials were tested and compared with commercial SMOX sensors under both controlled laboratory conditions and real-life conditions. Promising results were obtained, which showed that the prepared sensors performed similarly to the commercial sensors and exhibited excellent performance compared to the usual commercial sensors [33].…”
Section: Introductionmentioning
confidence: 81%